SISTEM KEPEGAWAIAN SEKOLAH: KUNCI EFEKTIVITAS DAN KUALITAS PENDIDIKAN - Framesti, Aldya; Nurhayati; Rahmawati, Ima (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2023)
This study examines the implementation of employee management systems at SMA Negeri 1 Dramaga using a qualitative descriptive method. The research focuses on the effectiveness of human resource management through five key stages: recruitment, training, performance evaluation, compensation, and career management. Findings reveal a rigorous selection process with micro-teaching tests, continuous training programs, and performance assessment systems based on employment status. The school implements standardized compensation for civil servants and provides promotion opportunities based on contribution. The research identifies primary challenges, including disparate treatment between civil servants and non-civil servants and infrastructure limitations. The conclusion emphasizes that an effective employee management system is crucial for enhancing educational quality.